A Bioinspired Stress‐Response Strategy for High‐Speed Soft Grippers (Adv. Sci. 21/2021). Issue 21 (3rd November 2021) - Lin, Yangqiao; Zhang, Chao; Tang, Wei; Jiao, Zhongdong; Wang, Jinrong; Wang, Wei; Zhong, Yiding; Zhu, Pingan; Hu, Yu; Yang, Huayong; Zou, Jun
Abstract : Bioinspired Stress‐Response Strategy The stress‐response strategy is a basic strategy of creatures. In article number 2102539, Yangqiao Lin, Jun Zou, and co‐workers demonstrate a bio‐inspired stress‐response strategy with passive sensing and actuating applied in a soft gripper, enabling the soft gripper to achieve repeatable passive high‐speed dynamic gripping with controllable trigger sensitivity, as well as active gripping with controllable force output.